Factors Associated with Safety Behavior Among Workers at PTPN IV Regional IV PKS Aurgading In 2024 - Meysha Aulia, Riana; Nurwaqiah Ibnu, Ismi; Kusmawan, David (Rifa'Institute, 2025)
Introduction: Safety behavior is an action taken by workers to prevent or even reduce the risk of work accidents. The high number of accidents is often caused by a lack of safety behavior in the work environment. There are several factors that influence safety behavior in workers, including knowledge, length of service, safety talk and safety climate. Purpose: This study aims to analyze the relationship between knowledge, length of service, implementation of safety talk and safety climate with safety behavior in workers at PTPN IV Regional IV PKS Aurgading. Method: This study is a quantitative study with a cross-sectional study design, the population in this study was 60 people, the sampling technique used was total sampling, and data analysis included univariate and bivariate with the chi square statistical test. Result and Discussion: Most workers 59.3% safe behavior while 40.7% unsafe behavior. There is a significant relationship between the implementation of safety talk and safety behavior (p = 0.003) and safety climate and safety behavior (p = 0.000). However, there is no significant relationship between knowledge and safety behavior (p = 0.210) and length of service and safety behavior (p = 0.548). Conclusion: Factors related to safety behavior include safety talk and safety climate, while those that are not related are knowledge and length of service